Inhibition of varicella-zoster virus-induced DNA polymerase by a new guanosine analog, 9-[4-hydroxy-2-(hydroxymethyl)butyl]guanine triphosphate. - Abele, G (1988)
The triphosphates of the antiherpesvirus acyclic guanosine analogs 9-[4-hydroxy-2(hydroxymethyl)butyl] guanine (2HM-HBG), 9-(2-hydroxyethoxymethyl)guanine (acyclovir [ACV]), and 9-(3,4-dihydroxybutyl)guanine (buciclovir) were examined for their effects on partially purified varicella-zoster virus (VZV) DNA polymerase as well as cellular DNA polymerase alpha. The triphosphate of 2HM-HBG competitively inhibited the incorporation of dGMP into DNA catalyzed by the VZV DNA polymerase. 2HM-HBG-triphosphate (2HM-HBG-TP) had a higher affinity for the dGTP-binding site on the VZV DNA polymerase than did dGTP; apparent Km and Ki values of dGTP and 2HM-HBG-TP were 0.64 and 0.034 microM, respectively. ACV-triphosphate (ACV-TP) was found to be the most potent inhibitor of VZV DNA polymerase. ACV-TP had a 14 and 464 times better direct inhibitory effect than 2HM-HBG-TP and buciclovir-triphosphate, respectively. The cellular (human embryonic lung fibroblast) DNA polymerase alpha inhibition was related to viral polymerase inhibition as efficacy ratios: 2HM-HBG-TP had a ratio of more than 1,000, which appeared to be similar to that of ACV-TP.